1983
DOI: 10.4315/0362-028x-46.7.578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduction and Replacement of Sodium Chloride on Rancidity Development in Raw and Cooked Ground Pork

Abstract: Ground pork (raw and cooked) was treated with NaCl, KCl or MgCl2 at ionic strengths of either 0.70 or 0.35, and stored at 4 or −20°C. Regardless of storage temperature, NaCl and MgCl2 increased rancidity of both raw and cooked samples, whereas KCl increased rancidity of raw samples only. In raw pork samples, NaCl increased rancidity the most. In cooked samples, MgCl2 increased rancidity more than NaCl when samples were stored at 4°C, but the opposite was true for samples stored at −20°C. Discoloration was most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 0 publications
0
36
1
2
Order By: Relevance
“…During 4-20 weeks of storage, the MA contents in the salted samples were significantly higher than those in the control samples. As has been observed in sardine and mackerel, [10][11][12][13][14][15] the addition of NaCl accelerated lipid oxidation in the yellowtail meats. Significant correlation was observed between the PC and MA contents during the 20 weeks (r ¼ 0:50 and p ¼ 0:013) (Fig.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…During 4-20 weeks of storage, the MA contents in the salted samples were significantly higher than those in the control samples. As has been observed in sardine and mackerel, [10][11][12][13][14][15] the addition of NaCl accelerated lipid oxidation in the yellowtail meats. Significant correlation was observed between the PC and MA contents during the 20 weeks (r ¼ 0:50 and p ¼ 0:013) (Fig.…”
mentioning
confidence: 71%
“…However, NaCl has been demonstrated to accelerate lipid oxidation in various meats, such as pork, [10][11][12] beef, 12) chicken, 12) and fish. [13][14][15] Kanner et al 12) reported that the pro-oxidative activity of NaCl is due to its ability to release iron from heme pigments and other heme binding molecules.…”
mentioning
confidence: 99%
“…Nevertheless, in some conditions, inhibition of lipid oxidation by NaCl has also been reported. For example, Rhee, Smith, and Terrell (1983) reported that NaCl activated lipid oxidation at low concentrations but inhibited it at concentrations greater than 2% in ground pork. In cooked turkey meat, previously prepared with 0 and 2% NaCl, King and Bosch (1990) detected significantly lower TBA values in samples with 2% NaCl than in meat with no added salt.…”
Section: Lipid Oxidationmentioning
confidence: 97%
“…Beriain et al (1993) Estes estudos apresentados indicam que a estabilidade lipídica em carnes e produtos cárneos é influenciada por diferentes fatores, dentre eles, a presença de catalisadores da oxidação lipídica, como luminosidade, temperatura, oxigênio, sal, espécie do animal, dieta, estado nutricional e idade do animal antes do abate, tipo de músculo (localização anatômica), manipulação da amostra (processamento, crua, cozida), além do método utilizado para as análises (RHEE et al, 1983).…”
Section: Resultsunclassified
“…As diferenças nos valores de TBA encontradas nesse trabalho podem estar relacionadas com as condições de armazenamento, tais como, luminosidade, fotoperíodo, temperatura ambiente, em torno de 30º C e/ou a presença de sal. O sal, adicionado durante a manufatura de vários produtos cárneos, tem sido responsabilizado como catalisador da oxidação lipídica, aumentando o número do TBA principalmente se estiver contaminado com metais (HUFFMAN et al, 1981;RHEE et al, 1983;SCHWARTZ;MANDIGO, 1985;Torres et al, 1988Torres et al, , 1989Asghar et al, 1990).…”
Section: Resultsunclassified